SELF-RELIANCE CHARACTERISTICS IN TAYLOR SWIFT'S SONGS: A STUDY ON LYRICS AND MESSAGES - Marwah Marwah; Deni Suswanto (Saksama: Jurnal Sastra, 2023)
This research aims to contribute to the exploration of self-reliance by examining the lyrics of Taylor Swiftâ€™s songs. This research intends to categorizing the data based on the kinds of self-reliance characteristics in Taylor Swift songsâ€™ lyrics and describing the contextual meanings which implied in Taylor Swiftâ€™s songsâ€™ lyrics. The data were collected from Taylor Swiftâ€™s album â€œLoverâ€, with a focus on three of her songs, including â€œThe Manâ€, â€œME!â€, and â€œYou Need to Calm Downâ€. The research employed a descriptive qualitative approach to analyze the data, which was obtained by a thorough examination of the lyrics and close listening to the songs. Subsequently, the data was classified according to the self-reliance concept proposed by Ralph Waldo Emerson. The study findings indicate the existence three different characteristics of self-reliance, including trust in oneself, nonconformity and independent thinking. Significantly, the most dominant of these characteristics was nonconformity, it found four lines of lyrics in all song which has examined. The study also identified two lines of lyrics in â€œThe Manâ€ and â€œME!â€ that express true in oneself characteristics, three lines of lyrics in â€œME!â€ and â€œYou Need to Calm Downâ€ that illustrate the independent thinking. The objective of this study is to make contribution to the current discourse on the important of self-reliance in modern society by examining the self-reliance characteristics found in Taylor Swiftâ€™s songsâ€™ lyrics. Furthermore, the result of this study may have implication for the role of music, art and literary work in promoting values such as individualism, self-reliance and nonconformity.